The S-Score of financial sustainability for professional football clubs - Evans, R. (Journal of Sports Economics, 2024)
This article extends the extensive literature on business failure and develops the approach of Altman to provide quantified recommendations for the financial sustainability of football clubs. The article uniquely identifies four scenarios that have caused insolvency for football clubs in the English Football League (EFL) and uses multiple discriminant analysis to identify financial models that delineate between professional football clubs that experience insolvency events and those that do not. These models produce an S-score which is introduced to suggest minimum financial tolerances for accounting ratios that provide a reasonable level of resilience for the financial sustainability of clubs in each scenario. The results are relevant for academics and non-academics with an interest in the business of football, professional football clubs aiming to avoid financial distress, and specifically, the Regulator that the U.K. government has proposed for football in England.